Da cultura militar à folkcomunicação: A elasticidade da banda de música do Comando Militar da Amazônia - Jefferson Rodrigo da Silva; Jonas da Silva Gomes Júnior (Revista Internacional de Folkcomunicação, 2019)
This article discusses the music band of the Military Command of the Amazon (CMA), as a tool for interaction with the Manauara society. In this context, the band performs presentations in civil spaces, environments that demand a repertoire adapted as a prerequisite for establishing a relationship of understanding, that is, of communication with the public. Therefore, this article aims to explain the factors that lead the CMA band to appropriate elements of Amazonian folklore, popular culture and mass culture, thus becoming a folk-communicational manifestation through music.